2017
DOI: 10.22146/ijcn.19379
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh yogurt sinbiotik pisang terhadap kadar glukosa dan insulin tikus sindrom metabolik

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
6
0
7
Order By: Relevance
“…IGT blood glucose levels in respondents who were given yogurt in this study decreased / decreased (16%) than fasting blood glucose levels in respondents who were not given yogurt. The results of the study are consistent with the research which showed that there were significant differences in mean blood glucose levels between the control group and the intervention group after giving banana sinbiotic yogurt to mice with metabolic syndrome (Rahmawati et al, 2017).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…IGT blood glucose levels in respondents who were given yogurt in this study decreased / decreased (16%) than fasting blood glucose levels in respondents who were not given yogurt. The results of the study are consistent with the research which showed that there were significant differences in mean blood glucose levels between the control group and the intervention group after giving banana sinbiotic yogurt to mice with metabolic syndrome (Rahmawati et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…According to (Dany et al, 2013) stated that men are more at risk of experiencing i-IFG than women. The adult population in the world who suffer from metabolic syndrome based on the International Diabetes Federation (IDF) is 20-25%, namely 8-24.2% in the male population and 7-46.5% in the female population (Rahmawati et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2017) dengan pemberian pakan standar dan aquadest ad libithum dengan tambahan HFFD (High Fat Fructose Diet) secara oral. HFFD berupa minyak babi 2ml/200g BB tikus/hari, kuning telur bebek 1ml/200g BB tikus/hari, dan fruktosa murni 1ml/200g BB tikus/hari (Rahmawati et al, 2017). Pemberian HFFD tidak memengaruhi asupan pakan standar yang dikonsumsi tikus.…”
Section: Metodeunclassified
“…Prebiotik akan difermentasi oleh Bakteri Asam Laktat (BAL) untuk menghasilkan SCFA (Verbeke et al, 2015) yang berperan dalam meningkatkan ekspresi dari glucose transporter 4 (GLUT-4) (Yan dan Kolapo, 2015). Peningkatan ekspresi GLUT-4 akan meningkatkan sensitivitas insulin dan peningkatan glukosa darah ke dalam membran sel sehingga terjadi penurunan kadar glukosa darah (Rahmawati et al, 2017). Penurunan kadar glukosa darah juga dapat menyebabkan perbaikan produksi insulin sehingga dapat memperbaiki kondisi obesitas sentral (Gandhi, 2017).…”
Section: Hasil Dan Pembahasanunclassified